Is There a Precise Correlation between the Lengths of the Peritoneal Reflection and the Middle Rectal Valve? - Isaac José Felippe Corrêa Neto; Mariana Campello de Oliveira; Laercio Robles; Leonardo Marcos Lopes Santos; Alexander Sá Rolim; Rogério Freitas Lino Souza; Hugo Henriques Watté; Angelo Rossi da Silva Cecchini (Journal of Coloproctology, 2022)
Introduction Pelvic anatomy remains a challenge, and thorough knowledge of its intricate landmarks has major clinical and surgical implications in several medical specialties. The peritoneal reflection is an important landmark in intraluminal surgery, rectal trauma, impalement, and rectal adenocarcinoma. Objectives To investigate the correlation between the lengths of the middle rectal valve and of the peritoneal reflection determined with rigid sigmoidoscopy and to determine whether there are any differences in the location of the peritoneal reflection between the genders and in relation to body mass index (BMI) and parity. Design We prospectively investigated the location of the middle rectal valve and of the peritoneal reflection via intraoperative rigid sigmoidoscopy in colorectal cancer patients undergoing elective colorectal surgery. Results We evaluated 38 patients with a mean age of 55.5 years old (57.5% males) who underwent colorectal surgery at the coloproctology service of the Hospital Santa Marcelina, São Paulo, state of São Paulo, Brazil. There was substantial agreement between the lengths of the middle rectal valve and of the peritoneal reflection (Kappa = 0.66). In addition, the peritoneal reflection was significantly lower in overweight patients (p = 0.013 for women and p < 0.005 for men) and in women with > 2 vaginal deliveries (p = 0.009), but there was no significant difference in the length of the peritoneal reflection between genders (p = 0.32). Conclusion There was substantial agreement between the lengths of the peritoneal reflection and of the middle rectal valve, and the peritoneal reflection was significantly lower in overweight patients and in women with more than two vaginal deliveries.